2017
DOI: 10.1126/science.aai9372
|View full text |Cite
|
Sign up to set email alerts
|

Tudor-SN–mediated endonucleolytic decay of human cell microRNAs promotes G 1 /S phase transition

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression. Compared to miRNA biogenesis, pathways that mediate mature miRNA decay are less-well understood. We report that biologically functional miRNAs are degraded in human cells by the endonuclease Tudor-SN (TSN). In vitro, recombinant TSN initiates the decay of both protein-free and AGO2-loaded miRNAs via endonucleolytic cleavage at CA and UA dinucleotides, preferentially at scissile bonds located > five nucleotides from miRNA ends. Consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 32 publications
(23 reference statements)
4
107
0
Order By: Relevance
“…Our findings agree with the sequence alignment results, which suggest that SN1 and SN3 likely bear endonuclease activities (Li et al, 2008). However, they are not consistent with a truncation study showing that SN1 and SN4 in hTSN are crucial for endonuclease activity (Elbarbary et al, 2017b) (see Discussion).…”
Section: Critical Catalytic Residues In Ctsn Are Located In the Sn1 Asupporting
confidence: 72%
See 4 more Smart Citations
“…Our findings agree with the sequence alignment results, which suggest that SN1 and SN3 likely bear endonuclease activities (Li et al, 2008). However, they are not consistent with a truncation study showing that SN1 and SN4 in hTSN are crucial for endonuclease activity (Elbarbary et al, 2017b) (see Discussion).…”
Section: Critical Catalytic Residues In Ctsn Are Located In the Sn1 Asupporting
confidence: 72%
“…It has been shown that TSN degrades certain hyper-edited primary miRNA precursors (Yang et al, 2006), as well as a group of mature miRNAs with a preference to cleave at UA and CA dinucleotides (Elbarbary et al, 2017b). Inosine editing may loosen the base pairing of miRNA precursors and increase their exposure to degradation by TSN.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations